The Racial and Gender Differences in the Impact of Adverse Childhood Experiences on Juvenile Residential Placement. (July 2018) - Zettler, Haley R.; Wolff, Kevin; Baglivio, Michael; Craig, Jessica M.; Epps, Nathan
Research has demonstrated a relationship between adverse childhood experiences (ACEs) and a variety of juvenile offending outcomes. No study to date, however, has examined the relationship between ACEs and juvenile residential placement. The current study utilized a large sample of 4, 733 adjudicated juveniles in Florida in order to examine the relationship between ACEs and residential placement across gender and race/ethnicity. For the entire study sample, ACEs significantly increased the odds of residential placement by age 17. For males, ACEs significantly increased the odds of residential placement for Black and Hispanic males but had a null effect on White males. For females, ACEs were predictive of residential placement for Black females but not for White or Hispanic females. Consistent predictors of residential placement across demographic groups included the presence of antisocial peers, substance abuse issues, and anger problems.